Uso de palha de carnaubeira como cobertura morta em cultivares de alho precoce nas condições do semiárido tropical - Luís, Márcio Avelino Sinoia (Universidade Federal Rural do Semi-Árido, 2019)
Soil cover with plant material is a traditional cultural practice in the cultivation of garlic, especially among small producers, while the use of virus-free seed garlic is a recent technology that has been used in several garlic producing regions of Brazil, because it allows the exploitation of the maximum productive potential of the cultivars. Thus, an experiment was installed in the period from May to September of 2018 at Rafael Fernandes Experimental Farm, Alagoinha, Mossoró, RN, in order to assess the use of Carnaubeira straw as covering in early garlic cultivars in the conditions of Tropical Semiarid. The experimental design was of randomized complete blocks with four repetitions, in split plot. The plots were represented by the soil cover: with and without mulch using straw, and the subplots were represented by the garlic cultivars virus free Araguari, CatetoRoxo, Canela de Ema, Centralina, Gravatá and Branco Mossoró infected. The characteristics evaluated were: Emergency speed index, emergence percentage, plant height, number of leaves, cultural cycle, survival percentage, mean mass of bulbs, total and commercial productivity, classification of bulbs, number of cloves per bulb and cloves classification. Soil cover did not influence plant height, number of leaves and survival percentage; however it influenced the Emergency Speed Index and emergence percentage of the cultivars that were more efficient for sprouting in soil without cover. The mulch has promoted significant increases in mean bulb mass, total and commercial productivity for cultivar Gravatá. The cultivars Branco Mossoró and Centralina provided more leaves per plant and cloves per bulb, showing greater adaptability to the climatic conditions of the region. The soil cover promoted highest percentage of bulbs in classes 4, 5 e 6, indicating that the use of this practice was important to obtain bulbs with better commercial value
Keywords: Allium sativum L.; Cultivares; Mulching; Produtividade; Allium sativum L.; Cultivars; Mulching; Productivity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA